1998
DOI: 10.1055/s-2006-957384
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Leading Compounds for Chemotherapy of Human Immunodeficiency Virus (HIV) Infection

Abstract: Many compounds of plant origin have been identified that inhibit different stages in the replication cycle of human immunodeficiency virus (HIV): 1) virus adsorption: chromone alkaloids (schumannificine), isoquinoline alkaloids (michellamines), sulphated polysaccharides and polyphenolics, flavonoids, coumarins (glycocoumarin, licopyranocoumarin) phenolics (caffeic acid derivatives, galloyl acid derivatives, catechinic acid derivatives), tannins and triterpenes (glycyrrhizin and analogues, soyasaponin and analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
220
0
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(229 citation statements)
references
References 34 publications
1
220
0
8
Order By: Relevance
“…The antiviral activity of soyasaponin against the herpes simplex virus, human immunodeˆciency virus, human cytomegalovirus, and FluV A has been reported. [8][9][10][11] Since it has been reported that soyasaponin was recovered in 70z aqueous ethanol, we presumed that the antiviral activity of the hot-water extract of black soybean against Ad1 would have come from compound(s) other than soyasaponin. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiviral activity of soyasaponin against the herpes simplex virus, human immunodeˆciency virus, human cytomegalovirus, and FluV A has been reported. [8][9][10][11] Since it has been reported that soyasaponin was recovered in 70z aqueous ethanol, we presumed that the antiviral activity of the hot-water extract of black soybean against Ad1 would have come from compound(s) other than soyasaponin. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since acute respiratory tract diseases are mainly caused by infection from viruses such as the adenovirus, in‰uenza virus, and coxsackievirus, 7) we have presumed that the pharmacological eŠect of the black soybean extract on the disease might be due to antiviral activity. Concerning the antiviral activity of soybean, it has been reported that soyasaponin from the common yellowish soybean inhibited the replication of the herpes simplex virus, 8,9) human immuno-deˆciency virus (HIV), 8,10,11) cytomegalovirus, 8) and in‰uenza virus. 8) However, the speciˆc antiviral activity of the black soybean extract against respiratory illness viruses has not been previously investigated.…”
mentioning
confidence: 99%
“…This is followed by the trans-esterification of phosphodiester bonds, one strand of DNA cutting and joining the 5 'end of the cut to the processed viral 3'-end. These two steps, called processing 3 'and band transfer of DNA can be measured in vitro using a purified recombinant integrase and a 21-mer duplex oligonucleotide corresponding to the end-HIV U5 LTR sequence (Vlietinck et al, 1998). Using a 3D database of the National Institute of Cancer and the appropiate software (Chem-X), Neamati et al (1997) have identified two potential architectures of active pharmacophores for virensic acid and other depsidones such as physodic acid.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Diversos autores atribuem o efeito farmacológico do guaco à cumarina (Pedroso et al, 2008), sendo estas descritas com diversas atividades terapêuticas importantes, tais como, anti-inflamatória, imunossupressora, hipolipidêmico, relaxante vascular, anticoagulante, hipotensora, espasmolítica, antioxidante, antiofídica, inibição da replicação do vírus HIV-1, entre outros (Pereira et al, 1994;Hoult & Payá, 1996;Vlientinck et al, 1998). Além disso, a agência regulamentadora de medicamentos do Brasil (Anvisa) considera a cumarina como marcador químico da M. glomerata, e de acordo com a resolução RE 89, de 16 de março de 2004, que determina a lista de registro simplificado de fitoterápicos no Brasil, a dose diária recomendada para este marcador pode variar entre 0,525 e 4,890 mg.…”
Section: Atividades Farmacológicasunclassified